The Effect of Job Recognition and Development Opportunities on Loyalty and Job Satisfaction of Generation Z in Jakarta's Creative Industries - Mohammad Gifari Sono; Agus Yulistiyono; Nur Khotijah (West Science Interdisciplinary Studies, 2024)
This study investigates the influence of job recognition and development opportunities on job satisfaction and loyalty among Generation Z employees in Jakarta’s creative industries. Using a quantitative approach, data was collected from 230 respondents through a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM-PLS). The results show that both job recognition and development opportunities have significant positive effects on job satisfaction and loyalty. Development opportunities were found to have a stronger impact on job satisfaction, while job recognition also significantly influenced both outcomes. These findings highlight the importance of tailored human resource strategies that focus on recognizing employee contributions and providing career development pathways. Organizations in Jakarta’s creative industries can enhance retention and satisfaction by investing in these key areas.